Postpartum cerebral venous thrombosis associated with protein S deficiency: A case report (Indian Journal of Case Reports, 2020)
There is a decline in the levels of protein S during pregnancy due to an increase in its binding protein. Thus, protein S deficiency increases the risk of thrombosis and may lead to poor pregnancy outcomes. In the setting of a hypercoagulable state during pregnancy, it is difficult to interpret protein S levels when measured with other tests of thrombophilia in pregnancy. The rate of developing thrombotic events is higher in those pregnant females with a deficiency of any natural anticoagulant like protein S. We report the case of a recently delivered female with multiple intracranial hemorrhages and cerebral venous thrombosis associated with protein S deficiency. This case highlights the need to extensively identify all risk factors of thrombosis in newly delivered females for the early and effective management of postpartum thrombosis.